Monocyte-Platelet Aggregates Triggered by CD31 Molecule in Non-ST Elevation Myocardial Infarction: Clinical Implications in Plaque Rupture - Vinci, Ramona; Pedicino, Daniela; Bonanni, Alice; d'Aiello, Alessia; Pisano, Eugenia; Ponzo, Myriana; Severino, Anna; Ciampi, Pellegrino; Canonico, Francesco; Russo, Giulio; Di Sario, Marianna; Vergallo, Rocco; et al. (Frontiers in Cardiovascular Medicine, 2022)
Despite recent innovations in cardiovascular care, atherothrombosis is still a major complication of acute coronary syndromes (ACS). We evaluated the involvement of the CD31 molecule in thrombotic risk through the formation of monocyte-platelet (Mo-Plt) aggregates in ACS patients with no-ST-segment elevation myocardial infarction (NSTEMI) on top of dual anti-platelet therapy (DAPT). We enrolled 19 control (CTRL) subjects, 46 stable angina (SA), and 86 NSTEMI patients, of which 16 with Intact Fibrous Cap (IFC) and 19 with Ruptured Fibrous Cap (RFC) as assessed by Optical Coherence Tomography (OCT). The expression of CD31 on monocytes and platelets was measured. Following coronary angiography, 52 NSTEMI were further stratified according to thrombus grade (TG) evaluation. Lastly, a series of ex-vivo experiments verified whether CD31 participates in Mo-Plt aggregate formation. In NSTEMI patients, CD31 was reduced on monocytes and increased on platelets especially in NSTEMI presenting with RFC plaques compared to those with IFC lesions, and in high-TG patients compared to those with zero/low TG. Ex-vivo experiments documented an increase in Mo-Plt aggregates among NSTEMI, which significantly decreased after CD31 ligation, particularly in patients with RFC plaques. In NSTEMI, CD31 participates in Mo-Plt aggregate formation in spite of optimal therapy and DAPT, suggesting the existence of alternative thrombotic pathways, predominantly displayed in RFC patients.